2016
DOI: 10.1039/c5ra24547h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and rheological behavior of poly(1,2-butylene oxide) based supramolecular architectures

Abstract: In this work we present the synthesis of poly(1,2-butylene oxide) (PBO) functionalized with the complementary hydrogen bond forming groups 2,4-diaminotriazine (DAT) and thymine. PBO is a rubbery polymer. Due to its semi-polar nature PBO is expected to suppresses non-directed cluster formation of the supramolecular groups but not influence their directed interactions. For the synthesis of backbone functionalized polymers we developed a procedure which allowed randomly copolymerizing BO with 1,2-epoxy-7-octene u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 37 publications
(32 reference statements)
2
26
0
Order By: Relevance
“…An increased compatibility of thy and DAT was also achieved in the literature with poly(butyl acrylate) (PBA) as the matrix [19]. However, the strong rise in the T g by roughly 30 • C upon functionalization of the PBA polymer may be an indication for strong local effects as well, and it contrasts with the observations for the present PBO polymer [42]. In addition, PBO is a particularly interesting intermediate polar polymer because of its low T g (−65 • C) and an entanglement molecular weight around 8000 g/mol.…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…An increased compatibility of thy and DAT was also achieved in the literature with poly(butyl acrylate) (PBA) as the matrix [19]. However, the strong rise in the T g by roughly 30 • C upon functionalization of the PBA polymer may be an indication for strong local effects as well, and it contrasts with the observations for the present PBO polymer [42]. In addition, PBO is a particularly interesting intermediate polar polymer because of its low T g (−65 • C) and an entanglement molecular weight around 8000 g/mol.…”
Section: Introductionsupporting
confidence: 62%
“…In addition, PBO is a particularly interesting intermediate polar polymer because of its low T g (−65 • C) and an entanglement molecular weight around 8000 g/mol. Both are very similar to the apolar polyisoprene (PI) or natural rubber (NR) elastomers [42]. PBA, though with comparably low T g , on the other hand possesses an entanglement molecular weight of about 30,000 g/mol and does not show valuable elastomeric properties on its own.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…As reported in a previous study no sign of self -association was revealed for the thymine functionalized backbone. Instead, a more pronounced effect of the functionalization with DAT groups was observed for the short chains 9 .…”
Section: Linear Rheologymentioning
confidence: 89%
“…In semi-functionalized blends, d-PBO thy-80k was used instead of pure d-PBO 80k as it does not show any signs of homo-association. 9 In the first case the blend of semifunctionalized components (red below) shows a close to Rouse-like behavior at long times typical of a non-entangled polymer system. The Rouse-like behavior at intermediate frequency…”
Section: Figure 10: Storage and Loss Moduli For D-pbo Thy-80k And Pbomentioning
confidence: 99%